Prosperita poľnohospodárskej prvovýroby vybraných spoločností podnikajúcich v oblasti ekologického poľnohospodárstva na Slovensku - Fiľarská, Jana (Univerzita Pardubice, 2017)
Agriculture, as the most important human activity, is one of the sustainable uses and land management. Over the past decade, traditional agriculture started its organic farming. Production of business in the land without the use of chemicals is helpful in maintaining and restoring natural resources. Slovak agriculture has a long tradition and due to the fact that the majority of the population worked mainly in the sector. In Slovakia, the businesses started to work on organic farming early 90s. Under the influence of foreign companies supplying cheap and surplus food products and disappearance of most agricultural cooperatives in Slovakia, Slovak decreased agricultural production and thus revenue companies. Part of the agricultural company, is the accession of Slovakia to the European Union, undertook to manage the land in order to be adopted in accordance with the requirements of environmental protection. With the entry of Slovakia into the EU, companies can apply for assistance in the form of subsidies, grants or other assistance in the form of contributions from the funds of the Slovak Republic or the EU. Despite the support of SR or EU companies need to reassess their economic activities and use of selected methods appropriately and prevent possible financial bankruptcy.
Prosperity primary agricultural production of certain companies involved in organic farming in Slovakia
Keywords: agriculture; Beerman model; productivity; employees; costs; Q14